CONSERVATION STATUS ASSESSMENT OF THE ENDEMIC HIERACIUM S. STR. (ASTERACEAE) OCCURRING IN SICILY - Di Gristina, E.; Raimondo, F. M.; Domina, G. (Annali di Botanica, 2022)
The current status of the majority of apomictic taxa, and therefore their priorities for conservation, are poorly known, and consequently, they are neglected by conservationists. In Sicily 8 species and 4 subspecies of Hieracium s. str. occurs. Eleven taxa are endemic to the area, one has a wider distribution. These taxa were not evaluated within the recent project “Red List assessment of plants and fungi in Italy” because collectively considered with insufficient and unreliable distribution data. The global conservation status of the endemic Hieracium s. str. taxa occurring in Sicily was assessed here using the IUCN categories and criteria, on the basis of the data collected during field surveys over 10 years. Criteria A, B, C and D were used in assessments. The assessment of punctual endemic taxa considered the real threats to which populations are subjected. Overall, 6 Critically Endangered, 2 Endangered, 1 Vulnerable and 2 Least Concern taxa were assessed. The knowledge of taxa, currently small in size and isolated from each other, allows for the planning of differentiated conservation strategies.